Effect of Different T6 Heat Treatment Conditions on the Microstructure and Mechanical Properties of Al-7%Si-0.35% Mg (A356) Alloy for Use in Motorcycles - Reinaldo Almeida Rodrigues; João Carlos Martins da Costa; Antonio Claudio Kieling; Nayra Reis do Nascimento; Joaquim Souza de Oliveira; Joziane Silva da Cunha; Samantha Coelho Pinheiro; Gilberto Garcia del Pino; José Luis Valin Rivera; Meylí Valin Fernández; José Costa de Macedo Neto (Metals, 2025)
This research presents the results of different periods of T6 heat treatment (homogenization and artificial aging) for A356 aluminum alloy used in the fabrication of motorcycles. The samples were cast using gravity die casting, and industrial furnaces for T6 were used in the experiment. Two heat treatment conditions were used, with a total time of 7 h and 12 h, and the results were compared with the alloy without heat treatment. The effects of the reduction of treatment time on mechanical behavior were evaluated in terms of hardness, Charpy and tensile tests, as well as morphological analysis of fractures and microstructural behavior via optical microscopy, SEM-EDS, measurement of eutectic Si evolution, and XRD. Excellent mechanical properties were achieved with a treatment period of 7 h, which achieved a yield strength of 226.58 (±3.76) MPa, tensile strength limit of 264.78 (±4.27) MPa and elongation of 3.41 (±0.47) %. This is competitive with other cast alloys subjected to T6 heat treatment in longer treatment cycles. The peak of hardness and highest impact resistance was recorded for the sample treated for 12 h; however, in the impact test, there was no significant difference between the two experiments.